2005
DOI: 10.1136/aim.23.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Direct to Spinal Nerves as an Alternative to Selective Spinal Nerve Block in Patients with Radicular Sciatica – a Cohort Study

Abstract: We applied electroacupuncture to the spinal nerve root by inserting needles under x ray imaging in three cases with radicular sciatica, as a non-pharmacological substitute for lumbar spinal nerve block. In all three cases, symptoms were markedly reduced immediately after electroacupuncture to the spinal nerve root. The sustained effect was noticeably longer than that of spinal nerve blocks previously performed, in two out of the three cases. We suggest that descending inhibitory control, inhibitory control at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Several previous studies showed that EA inhibited the primary afferent transmission of neuropathic pain [30] and that deep EA stimulation improved the pathological changes and function of the injured sciatic nerve in rats [31]. Other studies have suggested that descending inhibitory control, changes in nerve blood flow, or the inhibition of activity by nerve endings may be involved in the mechanism associated with the efficacy of EA [32]. Long-lasting alleviation of pain has been suggested to be closely related to the muscle tension improvement provided by EA [33].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies showed that EA inhibited the primary afferent transmission of neuropathic pain [30] and that deep EA stimulation improved the pathological changes and function of the injured sciatic nerve in rats [31]. Other studies have suggested that descending inhibitory control, changes in nerve blood flow, or the inhibition of activity by nerve endings may be involved in the mechanism associated with the efficacy of EA [32]. Long-lasting alleviation of pain has been suggested to be closely related to the muscle tension improvement provided by EA [33].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research has shown that acupuncture analgesia may be initiated by stimulation of high-threshold, small-diameter nerves in the muscles [37]. A cohort study found that after electroacupuncture (EA) to the spinal nerve root, the symptoms of patients with radicular sciatica were immediately and markedly reduced [38]. Animal experiments have revealed that acupuncture is a better treatment for regeneration of crushed sciatic nerves than diclofenac sodium [39].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Byrn et al 27 compared injections of saline solution and distilled water and reported that distilled water was more effective. Furthermore, in patients with radicular sciatica for which nerve root block was ineffective, Inoue et al 28 found that electroacupuncture stimulation in the nerve root region gave more favourable results than anaesthesia. All these reports indicate that stimulation therapy is more effective, supporting the results of our trial.…”
Section: Discussionmentioning
confidence: 99%